2009
DOI: 10.1292/jvms.71.891
|View full text |Cite
|
Sign up to set email alerts
|

Serological Studies of Infectious Bronchitis Vaccines against Japanese Field Isolates of Homologous and Heterologous Genotypes

Abstract: ABSTRACT. The genetic diversity of the partial S1 gene involving the hyper variable region for infectious bronchitis (IB) vaccine strains in Japan were compared with those of IB virus isolated from the field in Japan. Field isolates have mainly been classified into three major genotypes, JP-I, JP-II and JP-III, since 2003; however, the 4/91 genotype was detected from recent field isolates in Japan. The virus neutralization (VN) activity with vaccine immunized serum was investigated to evaluate the protective e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Sequence analysis of Sulaimani isolate S1 gene revealed its close relatedness only to three field isolates in Israel and Egypt (Table 2). Since high rate of antiserum immunized with different homologous field genotype could neutralize each other (Shimazaki et al, 2009;Wang and Huang, 2000), which suggest genotypes based on S1 sequence analysis to some extent correlate with serotypes of IBV strains, therefore Isolates from Egypt, Iraq and Israel can be considered as the same novel Middle East genotype, and most likely to be the same serotype.…”
Section: Discussionmentioning
confidence: 99%
“…Sequence analysis of Sulaimani isolate S1 gene revealed its close relatedness only to three field isolates in Israel and Egypt (Table 2). Since high rate of antiserum immunized with different homologous field genotype could neutralize each other (Shimazaki et al, 2009;Wang and Huang, 2000), which suggest genotypes based on S1 sequence analysis to some extent correlate with serotypes of IBV strains, therefore Isolates from Egypt, Iraq and Israel can be considered as the same novel Middle East genotype, and most likely to be the same serotype.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that the detection of 4/91 strains in Japan began after marketing of the 4/91 vaccine in this country. Shimazaki [14] reported that one of the 4/91 isolates in Japan might be derived from the vaccine, and others have been closely linked to French and Spanish isolates. In the U.S.A., after the introduction of a new vaccine from the Netherlands, a new IBV variant became endemic, and the S1 gene sequence was highly homologous to that of the vaccine strain [13].…”
Section: Discussionmentioning
confidence: 99%
“…This vaccine could be predicted in accordance with the genotype of field isolates. And since the S1 glycoprotein is responsible for infection of host cells, consequently the S1 protein is usually used for IBV typing [67] . Combination of antigenic epitopes of B cells and T cells that are conserved across many strains as a approach to evoke humoral and cytotoxic T cell (CTI) immune responses will potentially lead to a broad -based vaccine that could reduce the challenges in using live attenuated vaccine technology in the control of IBV infection in poultry .…”
Section: Designing Of Vaccine Epitopesmentioning
confidence: 99%